Brain iron accumulation affects myelin-related molecular systems implicated in a rare neurogenetic disease family with neuropsychiatric features - Heidari, M.; Johnstone, D.; Bassett, B.; Graham, Ross; Chua, A.; House, M.; Collingwood, J.; Bettencourt, C.; Houlden, H.; Ryten, M.; Olynyk, John; Trinder, D.; et al. (2016)
The ‘neurodegeneration with brain iron accumulation’ (NBIA) disease family entails movement or cognitive impairment, often with psychiatric features. To understand how iron loading affects the brain, we studied mice with disruption of two iron regulatory genes, hemochromatosis (Hfe) and transferrin receptor 2 (Tfr2). Inductively coupled plasma atomic emission spectroscopy demonstrated increased iron in the Hfe-/- × Tfr2mut brain (P=0.002, n =5/group), primarily localized by Perls’ staining to myelinated structures. Western immunoblotting showed increases of the iron storage protein ferritin light polypeptide and microarray and real-time reverse transcription-PCR revealed decreased transcript levels (P<0.04, n =5/group) for five other NBIA genes, phospholipase A2 group VI, fatty acid 2-hydroxylase, ceruloplasmin, chromosome 19 open reading frame 12 and ATPase type 13A2. Apart from the ferroxidase ceruloplasmin, all are involved in myelin homeostasis; 16 other myelin-related genes also showed reduced expression (P<0.05), although gross myelin structure and integrity appear unaffected (P>0.05). Overlap (P<0.0001) of differentially expressed genes in Hfe-/- × Tfr2mut brain with human gene co-expression networks suggests iron loading influences expression of NBIA-related and myelin-related genes co-expressed in normal human basal ganglia. There was overlap (P<0.0001) of genes differentially expressed in Hfe-/- × Tfr2mut brain and post-mortem NBIA basal ganglia. Hfe-/- × Tfr2mut mice were hyperactive (P<0.0112) without apparent cognitive impairment by IntelliCage testing (P>0.05). These results implicate myelin-related systems involved in NBIA neuropathogenesis in early responses to iron loading. This may contribute to behavioral symptoms in NBIA and hemochromatosis and is relevant to patients with abnormal iron status and psychiatric disorders involving myelin abnormalities or resistant to conventional treatments.